Pancasila sebagai Landasan Etis bagi Mahasiswa Keperawatan dalam Menggunakan Media Sosial - Matang, Matang (Indonesian Character Journal, 2025)
Pancasila as the nation’s worldview holds an important role in shaping character. The values contained within the principles of Pancasila provide a moral foundation for nursing students in carrying out their duties and responsibilities, especially when working in the digital era marked by the advancement of information and communication technology in healthcare services. Prospective nurses are faced with challenges in nursing practice to ensure that humanitarian and professional principles are not compromised. This study examines how Pancasila can serve as a foundation in shaping the ethics of students in the digital era and highlights the importance of reinforcing Pancasila values. Using a qualitative method, data were collected through semi-structured interviews with 13 informants selected through purposive sampling. The results show that nursing students frequently use social media platforms such as Instagram and TikTok. The most relevant Pancasila principles in the nursing profession are the first, second, and fifth principles. Although these values are important, their implementation is often neglected in the use of social media, particularly concerning nurses’ moral responsibilities, such as keeping patient privacy. Therefore, it is crucial to pay attention to Pancasila values when selecting and curating content before posting, in order to use social media appropriately and meaningfully.